Development Of Stem Integrated Lkpd to Improve the Critical Thinking Ability of Class X Students - Syarif, Ratih Ulfah R; Prasetyo, Erwin; Donuata, Pujianti Bejahida (Lembaga Riset Mutiara Akbar, 2023)
This study aims to develop STEM-integrated LKPD in order to train students' critical thinking skills on Newton's law of gravity material so that it is feasible to use. The feasibility of LKPD is seen from the validity, practicality and data n-gain index. The research method used is a 4-D development model consisting of Define, Design, Develop, and Disseminate, but in this study it only reached the develop stage. The validity of LKPD is seen from completeness, content, presentation and language. Practicality can be seen from the responses and activities of students when learning using LKPD. This effectiveness can be seen from the increase in the test results of students' critical thinking skills which were tested limited to 28 students. Research data were analyzed in a quantitative descriptive manner. The results of the validity of LKPD are stated to be very valid with a percentage of 88.9%. LKPD is stated to be very practical with a percentage of 90%. The results of increasing critical thinking skills are expressed by an average n-gain score of 0.61 in the Medium category. From the results of the validity, practicality and n-gain index data, the LKPD developed is feasible to use.